A two-sample bidirectional Mendelian randomization analysis between telomere length and hyperthyroidism - Zhu, Shiben; Hao, Ziyu; Chen, Qihang; Liu, Xiaoliu; Wu, Wenyan; Zhang, Fang (Frontiers in Endocrinology, 2025)
Backgroundhyperthyroidism characterized by low thyrotropin, highlighting complications and risks, including cardiac issues, osteoporosis, adverse pregnancy outcomes, unintentional weight loss, and increased mortality associated with untreated hyperthyroidism. However, the casual association between telomere length (TL) and hyperthyroidism remains unclear.ObjectiveWe aim to explore the casual relationship between TL and hyperthyroidism.MethodsA two-sample bidirectional Mendelian randomization (MR) analysis employed the inverse variance weighted (IVW) method, supplemented by additional approaches such as Weighted Median (WM), and MR Egger.ResultsThe summary statistics for TL were derived from the UK Biobank, comprising 472,174 individuals, while the data for hyperthyroidism were sourced from the GWAS Catalog and the FinnGen database, encompassing cohorts of 460,499 and 173,938 individuals, respectively. Utilizing 139 genome-wide significant single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) for TL, forward MR analyses indicated a negative causal effect of TL on hyperthyroidism. The risk of hyperthyroidism decreased as genetically predicted TL increased by one standard deviation, as determined by the IVW form GWAS Catalog (OR:0.659,95%CI: 0.541-0.802, p <0.001) and IVW from FinnGen(OR:0.634, 95%CI: 0.479-0.840, p = 0.001). Other MR methods exhibited a consistent trend in the impact of TL on hyperthyroidism. Reverse MR analysis suggested no causal association between TL and hyperthyroidism (p > 0.05). Sensitivity analyses confirmed the robustness of these results, suggesting minimal susceptibility to confounding factors and bias.ConclusionThe finding that longer telomeres reduce hyperthyroidism risk highlights the need to validate hyperthyroidism’s impact on telomere length, offering valuable insights for prevention and treatment.